Evaluasi Program Uji Tingkat Kompetensi (UTK) Departemen Otomotif SMKN 1 Blitar Menggunakan Model CIPPO - Wayan, Dodik; Isnandar, Isnandar; Widiyanti, Widiyanti (BRILIANT: Jurnal Riset dan Konseptual, 2024)
Vocational education is a form of education that prepares students to be ready to enter the world of work in certain fields of work. Currently, the development of Vocational High Schools (SMK) as providers of formal vocational education programs refers to the Merdeka Curriculum, one of which is to improve the relationship between schools and the world of work through the concept of links and matches between schools and industries. Competency Level Test (UTK) is a vocational education development program in the form of learning and competency testing developed by the Automotive Department of SMKN 1 Blitar. This study aims to determine the effectiveness of UTK quantitatively with indicators of context, input, process, product, and outcome aspects. This research is an evaluation study through a descriptive quantitative approach and survey through the CIPPO model (context, input, process, product, outcome). The population in this study were students and alumni using non-probability sampling techniques. The results showed the percentage of the quality level of the context aspect 97.8%; input aspect 92.2%; process aspect 93.8%; product aspect 96.9%; and outcome aspect 97.2%; meaning that the UTK program of the Automotive Department of SMKN 1 Blitar is effective as a student competency test program.